2002
DOI: 10.1177/109019810202900307
|View full text |Cite
|
Sign up to set email alerts
|

Using Community-Based Participatory Research to Address Social Determinants of Health: Lessons Learned from Seattle Partners for Healthy Communities

Abstract: Seattle Partners for Healthy Communities (SPHC) is a multidisciplinary collaboration of community agencies, community activists, public health professionals, academics, and health providers who conduct research aimed at improving the health of urban, socioeconomically marginalized Seattle communities. SPHC uses a community-based participatory research approach to address social factors that affect the health of these communities. This article describes three SPHC projects that focus on social determinants of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0
8

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(54 citation statements)
references
References 36 publications
2
44
0
8
Order By: Relevance
“…[88][89][90] Dissemination of research findings is also reported as gaining from PPI networks to increase access to peers 81 and relevant sections of the community, 15 and making information more broadly readable. 31,72 There are fewer published claims for PPI as playing a significant role in implementing findings, but, in a US public health research programme, Krieger et al 86 report PPI-related implementation of changes by increasing their cultural relevance. Several researchers have identified that PPI has helped them address ethical dilemmas, 17,71,78,85,91 for example ethically appropriate ways of contacting women with recently diagnosed breast cancer and the use of routine patient data.…”
Section: Patient and Public Involvement: The Methodological Argumentmentioning
confidence: 99%
See 4 more Smart Citations
“…[88][89][90] Dissemination of research findings is also reported as gaining from PPI networks to increase access to peers 81 and relevant sections of the community, 15 and making information more broadly readable. 31,72 There are fewer published claims for PPI as playing a significant role in implementing findings, but, in a US public health research programme, Krieger et al 86 report PPI-related implementation of changes by increasing their cultural relevance. Several researchers have identified that PPI has helped them address ethical dilemmas, 17,71,78,85,91 for example ethically appropriate ways of contacting women with recently diagnosed breast cancer and the use of routine patient data.…”
Section: Patient and Public Involvement: The Methodological Argumentmentioning
confidence: 99%
“…However, there was no evidence on how this affected research outcomes. This effect of PPI on study recruitment has been reported widely elsewhere, 70,[78][79][80][81][82][83][84][85][86]88 but the range of case studies within the RAPPORT study allows the specific components to be teased out ( Figure 19). …”
Section: Linking To the Wider Communitymentioning
confidence: 99%
See 3 more Smart Citations